Efektivitas campuran ekstrak daun kari (Murraya koeginii) dengan daun sirsak (Annona murricarta linn) sebagai insektisida dalam menghentikan larut rumah (Musca domestica) - Syahrizal Syahrizal; Junaidi Junaidi (Jurnal SAGO Gizi dan Kesehatan, 2021)
Background: Flies (Musca domestica) can act as vectors of typhus, dysentery, and cholera. Various methods have been used to control flies from around human life, either mechanically (light traps), a chemical in the form of toxic baits or insecticides, or with scents that are repellent. A mixture of curry leaf extract with soursop leaves can be used as an insecticide to repel house flies. Because curry leaves and soursop leaves contain compounds, tannins, saponins, and flavonoids that flies do not like.Objective: The purpose of this study was to determine the effectiveness of a mixture of curry leaves with soursop leaves as a natural insecticide in repelling the flies (Musca Domestica).Methods: This research is an experimental design with a mixture of curry leaf extract with soursop leaves on the power of repelling house flies. This research was conducted in 2019 in Darul Kamal District, Aceh Besar. The object of the research was 450 house flies, which consisted of five treatments with three repetitions. Data analysis was carried out with the one-way ANOVA statistical test.Results: The descriptive results showed that at a dose of 10gr/100ml the average flies were able to repel 37 flies, at a dose of 20 gr/100ml were 44, at a dose of 30 gr/100ml were 59 and at a dose of 40 gr/100ml was 70. Of the four treatments, the most effective dose was at a dose of 40gr/100ml, which was 70 (77.7%). Statistically, it showed that there was a significant difference (p < 0.05) between various doses/treatments of mixed extracts of curry leaves (Murraya koeginii) and soursop leaves (Annona muricata Linn) on the repelling power of house flies (Musca domestica), with p-value = 0.000.Conclusion: A mixture of curry leaf extract (Murraya koeginii) with soursop leaf (Annona muricata Linn) is effective as an insecticide in repelling house flies (Musca domestica).